BichoBot – A Chatbot to Assist in the Reception of Incoming University Students - Nascimento, Sheiely do Ó; Gonçalves, Enyo; Oliveira, Marcos; Barros, Erlânio Freire (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
The beginning of the journey in a higher education course is often surrounded by doubts from incoming students about various topics such as scholarship policies, course characteristics, library use, university restaurant, among other aspects of university life. Information about these topics is often found on different websites and documents, which makes it difficult for incoming students to find. Given this difficulty, actions that centralize this information to help students identify it become necessary. Thus, in this context, this article presents BichoBot, a chatbot developed to support freshmen in accessing institutional information at the Federal University of Ceará (UFC) - Quixadá Campus. BichoBot involves the use of the Rasa and RAG frameworks, with a LLaMA 3 language model. BichoBot offers contextualized and reliable answers via Telegram. The proposed solution was evaluated by UFC freshmen, demonstrating good performance in addressing the most common questions from students.